Su un maestro dal fare garbato. Una Madonna del Trecento e un raggruppamento di sculture lignee nelle Alpi orientali - Mor, Luca (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The article presents a polychrome wooden statue of the Madonna and Child in a private Belgian collection. The piece is attributed to the so-called Master of the enthroned St. Peter of Aufkirchen, active around 1330/40 in centres spread across Salzburg and the Eastern Alps. A consistent group of wooden sculptures in the same area outlines the Master’s artistic personality, influenced by works from the Upper Rhine, southern Germany and central Europe, highly indebted to French prototypes and executed between the last decades of the 13th century and the beginning of the 14th century. The relationship with Moravian wooden sculpture is emblematic; yet, our Master’s more conventional Gothic inclination is reliable to the artistic trend of Salzburg. Indeed, its archdiocese fostered contacts with the centres of the Empire and the nearby Tyrolean Alpine valleys.